2015
DOI: 10.1038/mi.2014.104
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin2 encourages inflammation-induced epithelial apoptosis through ER stress/PUMA in colitis

Abstract: β-Arrestins (β-arrs) are regulators and mediators of G protein-coupled receptor signaling, and accumulating evidence suggests that they are functionally involved in inflammation and autoimmune diseases. However, the effect of β-arrs is unclear in inflammatory bowel disease (IBD), and the role of β-arr2 is unknown in ulcerative colitis (UC) and Crohn's disease (CD). The aim of this study is to investigate whether β-arr2 encourages inflammation-induced epithelial apoptosis through endoplasmic reticulum (ER) stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
2
29
1
Order By: Relevance
“…This indicated that β-arrestin2 promoted 5-FU-induced apoptosis in colon cancer cells. In a previous study by Zeng et al (29) it has been proved that β-arrestin2 promotes inflammation-induced epithelial apoptosis through ER stress/PUMA in colitis. Liu et al (17) demonstrated that β-arrestin2 deficiency was associated with radiation-induced intestinal crypt progenitor cell apoptosis through protracted NF-κB activation and suppression of PUMA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This indicated that β-arrestin2 promoted 5-FU-induced apoptosis in colon cancer cells. In a previous study by Zeng et al (29) it has been proved that β-arrestin2 promotes inflammation-induced epithelial apoptosis through ER stress/PUMA in colitis. Liu et al (17) demonstrated that β-arrestin2 deficiency was associated with radiation-induced intestinal crypt progenitor cell apoptosis through protracted NF-κB activation and suppression of PUMA.…”
Section: Discussionmentioning
confidence: 95%
“…Accumulating evidence has uncovered the role of β-arrestin2 in apoptosis (23,24) and the dual effect of β-arrestin2 in apoptosis (24)(25)(26)(27). Under different conditions, β-arrestin2 can be pro-apoptotic or anti-apoptotic (28)(29)(30). In the present study, 5-FU, as a core drug for CRC, was selected as a drug-interfering factor.…”
Section: Discussionmentioning
confidence: 96%
“…β-arrs are involved in several types of diseases, including Parkinson’s disease, multiple sclerosis, cardiovascular conditions, and colitis by serving as a scaffold protein in various signaling pathways, including ERK1/2, Wnt/β-catenin and c-Src 1517 . Previously, we discovered that β-arr2 contributed to the development of experimental colitis and mucosal repair in the process of UC 18, 19 . In addition to their role in receptor downregulation, β-arrs also act as scaffold proteins to accelerate signal transduction in the EP4 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These authors found β-arr2 expression to be a susceptibility factor in colitis (28). They demonstrated in cell culture studies that, β-arr2 binds eIF2α and induces ER stress thereby affecting epithelial apoptosis through p53-upregulated modulator of apoptosis (PUMA).…”
Section: Discussionmentioning
confidence: 99%